Differences in Providing Education Using Poster Media and Audiovisual Media on Prevention of Rabies Transmitting Animal Bites - Achjar, Komang Ayu Henny; Asih, Putu Tarma; Lestari, Agus Sri; Gama, I Ketut; Ribek, I Nyoman (Journal of Education Reseach and Evaluation, 2023)
Rabies is an acute infectious disease that attacks the nervous system in humans and warm-blooded animals caused by the rabies virus, transmitted through the saliva of rabid animals such as dogs, cats, monkeys, raccoons and bats through bites or open wounds. The aim of the research is to analyze the differences in providing education using poster media and audiovisual media on behavior to prevent bites from animals that transmit rabies. The type of research used was pre-experimental designs with a two-group pre-test and post-test without control group design. The sampling technique used is non-probability sampling, namely purposive sampling. The number of samples used in this research was 86 families divided into 2 groups, namely the poster group and the audiovisual group. This research used a questionnaire sheet to measure the behavior of preventing bites from animals that transmit rabies, which consists of 3 sub-variables, namely knowledge, attitudes and actions. Then it was analyzed using the Mann-Whitney test to analyze the differences between educational poster media and audiovisual media. The research results show that the average value for poster media before is 65.6 and after is 77. Meanwhile, the average value for audiovisual media before is 72.2 and after is 82.3. Statistical testing used the Mann-Whitney test and obtained a ρ−value of 0.001 < 0.05. The conclusion is that there is a difference between providing education using poster media and audiovisual media on behavior to prevent bites from animals that transmit rabies. Suggestions to respondents are that they can provide education to those closest to them or anyone who is advised to use audiovisual media.